Analisis Rencana Strategis Sumber Daya Manusia (SDM) Keperawatan Di Rumah Sakit Wilayah Jakarta - Pinandhika Jayawisastra; MEYLLY SUMAMPOUW; VERONICA CHAIN; Puji Lestari; Widiya Yulian Situmeang (Politeknik Karya Husada, 2023)
Background. A Hospital Information System (SIMRS) that is made without good planning results in existing information being difficult to integrate, ineffective and inefficient and can result in losses for the organization. So that strategic planning is needed for hospitals as an organizational reference for achieving goals and objectives, thereby optimizing the achievement of objectives, placing the organization in an optimal position in a more competitive environment, assisting organizations in formulating a better strategy through a more systematic, logical approach. and rational.Objective. Describe the strategic plan for the Nursing Management Information System (SIMK) of RSU X, analyze the data, and make recommendations for developing a Nursing Management Information System (SIMK) strategic planning design.Method. Done with the case study method with an analytical approachStrength-Weakness-Opportunity-Threat (SWOT) and develop a strategy on the matrixThreat-Opportunity-Weakness-Strength (TOWS) and perspectivesBalance Score Card (BSC). Results.The results of the analysis of RSU X on the Internal External (IE) matrix, namelygrowth and build strategy where hospitals need strategies to grow better and be able to develop SIMK to get service optimization through perspectiveBalanced Score Card (BSC) andKey Performance Indicators (KPI) by setting the goals for the management and development of SIMRS-SIMK, the formation of competent and high-integrity nursing staff in the implementation of SIMRS-SIMK, optimizing the use of SIMRS that has beenbridging with the National Health Insurance system, the realization of SIMK which is integrated with SIMRS, the existence of internal policies that support the implementation of SIMK, increasing service quality and providing customer consulting services, providing patient satisfaction surveys onlineonline and integrated into all departments, availability of a list of Information and Technology (IT) risks that must be managed by the hospital, optimization of the SIMRS security system, and optimization of the SIMRS implementation monitoring and evaluation system in relation to quality and cost control.Conclusion. Hospital Information Systems that are integrated with Nursing Management Information Systems are the most important productivity factors in hospitals because they affect the performance and services provided by hospitals. Nursing Management Information Systems that are made with good planning will produce information that is integrated, effective, efficient, and directed. It is hoped that management can create a reliable SIMK and synergize with technological developments to increase professionalism.